Investigations on the foetotoxic effect of fumonisin B1 in pig and rabbit - Kovács, Melinda; Romvári, Róbert; Orova, Zoltán; Kovács, Ferenc; Horn, Péter (Acta Agraria Kaposváriensis, 2003)
The aim of the study was to examine the foetotoxic effect of fumonisin B1(FB1), the main mycotoxin of Fusarium moniliforme, in pig and rabbits. Pig was examined because the harmful effects of fumonisin toxicosis manifests in sever animal health problems and economic losses mainly in pig production. Rabbit was used as human model. In the first experiment three sows were fed a diet mixed with Fusarium moniliforme fungal culture from the 107th day of the pregnancy in a daily dose of 300 mg. The toxin containing diet was administered to two sows for an additional 7 days subsequent to parturition (i.e., for a total 14-16 days). The third sow was fed toxin free diet after parturition. Two piglets were examined from each of the three sows immediately after parturition (i.e., prior the first suckling), after 24 h and finally, on the 7th day postparturition. It was established that the typical pathological changes indicating fumonisin toxicosis (i.e., pulmonary oedema) was developed in all of the piglets already at birth. On the 7th day in the piglest of the third sow, the diet of which contained no toxin after parturition, no changes were observed. AST and ALKP activities were higher than the physiological limits. The SA/SO values of the serum were in correspondence with the severity of the pathological changes. In the second experiment 16 (10 treated with FB1 and 6 controls) Pannon White rabbits, being in the 25th - 30th days of pregnancy, were given 5 mg/animal/day FB1 solution, extracted from the fungal culture of Fusarium moniliforme. Foetuses were examined on the 28th and 30th day of pregnancy. Dissection of the does revealed pathological changes in the liver and kidney, in some cases the heart and the stomach showed alterations. In the foetuses liver and kidney were the target organs. When compared to controls, in treated animals significantly elevated ALKP, ALT and AST activities, creatinine and urea concentrations were measured both in does and foetuses. It was established, that FB1 crosses the placental barrier in pregnant sows and rabbits and is harmful for the foetuses. In pig the tipical disease, pulmonary oedeme was developed, while in rabbit it manifested in hepatic and renal injury.